Low Dose Aspirin and Mucoprotective Effects of Omeprazole and Ranitidine (Journal of Armed Forces Medical College, Bangladesh, 2011)
Omeprazole and ranitidine are widely used in the treatment of peptic ulcer disease and in association of Nonsteroidal Anti-inflammatory Drugs (NSAIDs) to prevent the mucosal injury of gastrointestinal tract. In the light of above, the study was undertaken to assess the superiority of omeprazole over ranitidine in the protection of mucosal injury caused by low dose aspirin. This is a prospective and comparative study carried out among the people taking low dose aspirin along with either omeprazole or ranitidine at gastroenterology centre of a military hospital over a period of 52 weeks. Respondents were recruited consequently and data were collected on specific data collection sheet with relevant clinical information and endoscopic findings. In ranitidine group 16 patients (40%) were found to have mucosal injury where as 05 patients (12.5%) in the omeprazole group were found to have gastroduodenal mucosal injury. The difference was statistically significant (p